From ICU to Emergency Department: 9-Year Experience with Non-Invasive Ventilation for COPD. Issue 3 (May 2014) - Ibrahim, I; Phua, J; Goh, EL; Mahadevan, M; Lim, TK
Introduction: Non-invasive ventilation (NIV) has been shown to be beneficial for chronic obstructive pulmonary disease (COPD) patients with persistent respiratory acidosis during acute exacerbations. This clinical study described the experience of implementing an NIV program in the emergency department for COPD patients. Methods: In the pre-implementation phase, patients who presented to the emergency department were transferred to the intensive care unit for NIV. Following the NIV program, patients had NIV commenced in the emergency department. We reported the change in hospital outcomes pre and post-implementation. Results: A total of 153 patients received NIV, 34 in the pre-implementation phase and 119 patients in the post-implementation phase. The mean pH was 7.22±0.07 and the Acute Physiology and Chronic Health Evaluation (APACHE) II score was 18.9±4. Hospital mortality was lower in the post-implementation phase (1.7% versus 11.8%; p=0.008). The median door-to-NIV time was shorter in the post-implementation phase (64 minutes; interquartile range [IQR] 35-113) versus (457 minutes; IQR 143-1320). Conclusions: NIV program in the emergency department is feasible and is associated with better hospital outcomes in patients with COPD. (Hong Kong j.emerg.med. 2014;21:140-147)